Temperature Dependence of Acidity Constants, a tool to affect separation selectivity in capillary electrophoresis - Reijenga, Jetse C. (2007)
The mathematical models of migration and dispersion in capillary zone electrophoresis of small molecules form a sound basis for separation strategies of complex mixtures. It turned out that the key property is the effective mobility of the sample ions. To tune resolution parameters such as pH, complexation constants and ionic strength are widely used; temperature however is not although mobilities and pKa values depend in a more or less degree on temperature. From the temperature dependences of pKa values of a number of compounds listed in the literature a general rule can be derived: for carboxylic and inorganic acids dpKa/dT values are very small and the pKa values change less than ±0.05 units/10 K. Thermodynamically speaking, these compounds exhibit dissociation enthalpies close to zero. Phenols and amines, on the other hand, have systematically larger dpKa/dT values of about −0.1 to −0.2 units per 10 K (the results of dissociation enthalpies of 20–70 kJ/mole). Based on this classification, a distinction can be made between different situations in capillary electrophoresis: (i) selectivity changes with temperature are largely due to the temperature dependence of the pKa of the buffering compound in the background electrolyte, (ii) selectivity changes mainly result from the temperature dependence of the pKa of the sample ions, and (iii) temperature effects on the pKa values of both, sample and buffer play a role. This work demonstrates such effects on selectivity in capillary electrophoresis highlighting the fact that in some instances temperature can be used to fine-tune separations.